Pelatihan Wirausaha Masyarakat Kampung Cilengkong Kecamatan Pamijahan-Bogor Untuk Menghadapi Masyarakat Ekonomi Asean (MEA) Dalam Mengoptimalisasikan Potensi Panen Singkong - Yulianti Yulianti; Dewi Ayu Kusumaningrum (Jurnal Sains Terapan Pariwisata, 2017)
The ASEAN Economic Community (MEA) can be a good marketing area for farmers with well-planned training and planned expertise. Due to the knowledge and skills that are always up to date certainly can create a competitive product but still pay attention to the value of local culture and using local raw materials. So it has its own uniqueness that is not owned by other countries. One of them is by preserving traditional food that is processed in a creative way. Local food ingredients such as cassava that can grow easily, quickly and efficiently. During this processed into several types of traditional cakes, but when viewed from the physical chemical properties of the material, cassava can be processed into raw material substitute wheat. Based on the information obtained, that the main producer of this village is cassava. So far, the harvest obtained by the villagers is generally sold directly to the market without any other process at a cheap price. This is the basis for the selection of training topics in this community service is processed products cassava harvest. Implementation of food processing training, product packaging and how to sell products with the theme "Cassava Build Cilengkong" was held in the Assembly Ta'lim Cilengkong, Pamijahan, Bogor regency, West Java. Operation for 1 day on Thursday, April 13, 2017. Training participants are PKK mothers, DKM mothers (Council of Mosque Prosperity), housewives. Attendees were 50 people. Implementation; Site Survey, Proposal Submission, Coaching Preparation, Implementation of Training Activities with training method of giving materials. Then proceed with the practice directly in the processing of cassava products in the form of coaching. So that participants can hone their skills directly. In this Training are proposed Plastic packaging suitable for use, the addition of packaging labels with attractive brand logo, material composition information, manufacturing date and expiration, storage method, production place and contact number. In this case the villagers are taught how to sell their products of creation by manual or online